Combustion stability study of partially premixed combustion with low-octane fuel at low engine load conditions. (1st February 2019) - An, Yanzhao; Raman, Vallinayagam; Tang, Qinglong; Shi, Hao; Sim, Jaeheon; Chang, Junseok; Magnotti, Gaetano; Johansson, Bengt
Highlights: Fuel-trapping in piston crevice was visualized in experiment for the first time. The ω-shape quartz piston and continuous-fire mode were used in optical test. Interaction among spray, piston, and cylinder wall was studied by laser diagnostic. The sensitivity of combustion to inlet temperature was studied for low-octane fuel. Fuel-trapping and injector dribbling was verified and linked to engine emissions. Abstract: The study aims to investigate the sensitivity of combustion stability to the intake air temperature for partially premixed combustion (PPC). The experiments were carried out in a full view optical engine at low load condition. The ω shape optical piston crown as same as the actual product piston, rather than the flat crown piston used in the previous study, was employed for the present experimental test. The continuous-fire mode rather than the skip-fire mode was used to run the optical engine ensuring the similarity to the actual engine operating conditions. The interaction among fuel spray jets, piston and cylinder wall was visualized by fuel-tracer planar laser-induced fluorescence. The high-speed combustion images were processed to determine the combustion stratification based on the natural flame luminosity. The combustion phasing, maximum in-cylinder pressure, and indicated mean effective pressure (IMEP) were compared at various intake temperatures. The results showed that the lower intake temperature could be used for achieving better combustion stability at low load condition along with the retarded CA50, the lower maximum in-cylinder pressure, and the higher IMEP. 70 °C was the lower limit of intake temperature to achieve stable PPC operation with the single-injection strategy. The same trend of the combustion characteristics with respect to the start of injection timing was confirmed at various intake temperatures. The combustion stratification analysis indicated more inhomogeneous low-temperature combustion with decreased natural flame luminosity and increased soot emission when the intake temperature reduced from 120 °C to 70 °C. Nitrogen oxides emission decreased when compared to the higher intake temperature cases at the expense of increased unburned hydrocarbon and carbon monoxide emissions at PPC mode. The fuel tracer measurements showed that most of the injected fuel hit on the piston top and only less amount of fuel was injected into the piston crown bowl at PPC mode due to the wider spray umbrella angle. The fuel trapped in crevice zone was verified as an important source for the unburned hydrocarbon and carbon monoxide emissions at PPC mode. The injector dribbling during the late stage of combustion attributed to soot formation. The injector with a relatively narrow spray umbrella angle was suggested for optimized interaction among the fuel spray jets, piston and the cylinder wall at PPC mode.